Desulfurization of Cysteine-Containing Peptides Resulting from Sample Preparation for Protein Characterization by MS - Wang, Zhouxi (2010)
In this paper, we have examined two cysteine modifications resulting from sample preparation for protein characterization by MS: (1) a previously observed conversion of cysteine to dehydroalanine, now found in the case of disulfide mapping and (2) a novel modification corresponding to conversion of cysteine to alanine. Using model peptides, the conversion of cysteine to dehydroalanine via β-elimination of a disulfide bond was seen to result from the conditions of typical tryptic digestion (37 °C, pH 7.0– 9.0) without disulfide reduction and alkylation.. Furthermore, the surprising conversion of cysteine to alanine was shown to occur by heating cysteine containing peptides in the presence of a phosphine (TCEP). The formation of alanine from cysteine, investigated by performing experiments in H(2)O or D(2)O, suggested a radical-based desulfurization mechanism unrelated to β-elimination. Importantly, an understanding of the mechanism and conditions favorable for cysteine desulfurization provides insight for the establishment of improved sample preparation procedures of protein analysis.